Estimasi Produksi Ikan Melalui Analisis Nutrien Seresah Mangrove Avicennia Sp. Di Kawasan Mangrove Information Center Wonorejo-Surabaya, Provinsi Jawa Timur - Indrawan, Rindya Fery; Hariyadi, Hariyadi (Universitas Mataram, 2025)
Mangrove forest is a very fertile ecosystem and is located in the coastline so that it has a major contribution to the surrounding environment. Mangrove tree litter that falls will be a food source for aquatic biota and nutrients that greatly determine the productivity of marine fisheries. The purpose of this study was to analyze the production of nutrients (N, P) from mangrove leaf litter, suspect the primary production of phytoplankton from nutrients released from mangrove leaf litter, and to estimate the carrying capacity of the mangrove ecosystem on fish production. This research station determination method uses a purposive randome sampling method with reference to the mangrove density and determination of the sampling point. Litter production measurements using themethod litter trap and decomposition rate using themethod litter bag. Estimation of fish production using the Beveridge (1984) method approach. The amount of nutrients released by mangrove Avicennia sp. per day at the mangrove Information Center which is 0.0350-0.0503 g N / m / day and the release of Phosphorus ranges between 0.0018-0.0053 g P / m2 / day. The value of primary production in the mangrove ecosystem information center Wonorejo-Surabaya is quite high ranging from 460 to 690 g C / m2 / yr, and is included in the category of fertile to very fertile. Herbivor fish production ranges from 462.04 to 690 kg / ha / yr; Carnivorous fish ranged from 46.20 to 69 kg / ha / yr and total fish production ranged from 595.80 kg / ha / yr. The total fish production illustrates the potential of fish production contributed from the mangrove ecosystem at 595.80 kg / year.